Performance analysis of water based photovoltaic thermal collector with serpen-direct absorber - Sachit, Fadhil Abdulameer (2021)
Solar energy is harvested as thermal and electrical energy with a solar thermal collector and a photovoltaic (PV) module, respectively. A PV thermal (PV/T) collector is a recently developed technology that can simultaneously produce electrical and thermal energy. The thermal collector cools down the back PV surface temperature to increase electrical efficiency. The thermal collector conveys this heat using a working fluid and extracts it as thermal energy. In this study, a new solar absorber design called serpen-direct was proposed and developed for a PV/T water system. The development based on a new configuration of tubes was used to maintain the water circulation inside the flow channel and achieve a uniform distribution temperature at the PV module surface. A threedimensional Navier–Stokes equation coupled with the energy balance equation of the PV/T model was solved on computational fluid dynamics ANSYS-Fluent software and MATLAB Simulink to perform numerical computations. In the numerical simulation, the effects of various operating and climate conditions were investigated to evaluate the performance of the PV/T module. Outdoor experiments were conducted under Malaysia’s climate conditions with a mass flow rate ranging from 0.033 kg/s to 0.098 kg/s. Indoor experiments were performed under 500 W/m2 to 1000 W/m2 solar irradiance with the same mass flow rate values of the outdoor experiments. Numerical results are in good agreement with the corresponding experimental outcomes. The effects of different operating and climatic conditions on the PV/T performance were analysed. The PV/T system was compared with conventional PV module. Mathematical results show that the highest daily average electrical efficiency values for the PV/T system and PV module are 12.17% and 11.36%, respectively, at a mass flow rate of 0.098 kg/s. The highest daily average thermal and total efficiency values for the PV/T system are 76.64% and 88.53%, respectively, at a mass flow rate of 0.082 kg/s. Simulation results show that the temperature cell gradient of the PV/T surface ranges from 56.6°C to 59.8°C, and experimental results range from 52.7°C to 57.9°C at a mass flow rate of 0.033 kg/s. Experimental results show that the highest thermal and total efficiencies of the PV/T system are 86.0% and 97.43%, respectively, at a mass flow rate of 0.082 kg/s. The highest daily average electrical efficiencies of PV/T and PV modules are 11.76% and 10.95%, respectively, at a mass flow rate of 0.098 kg/s. The mean absolute percentage error values of electrical, thermal and total efficiencies are 3.81%, 4.94% and 4.74%, respectively. The PV/T module’s gradient temperature is 4.94%. Results show that reduced cell temperature leads to improved output power and electrical efficiency of the PV/T collector. However, the increase in mass flow rate and solar irradiance leads to an increase in thermal and total efficiencies, but the thermal and total efficiencies decrease beyond the optimum value of mass flow rate at 0.082 kg/s.